Effect of chronic L-carnitine supplementation on carnitine levels, oxidative stress and apoptotic markers in peripheral organs of adult Wistar rats. (December 2019) - Kelek, Sevim Ercan; Afşar, Ebru; Akçay, Güven; Danışman, Betül; Aslan, Mutay
Abstract: This study investigated the effects of L-carnitine supplementation on carnitine levels, oxidative stress and apoptotic markers in the stomach, kidney, liver and testis tissues in adult rats. Rats were randomized to control and L-carnitine supplemented (LCAR) groups. Control group received distilled water for 7 months by intragastric gavage and the LCAR group was given 50 mg/kg/day L-carnitine via intragastric intubation for the same period. L-carnitine concentrations and caspase-3 activity were measured by fluorometric methods while cleaved caspase-3 was determined by Western blot analysis. Bcl-2 associated X protein (Bax) and B-cell lymphoma/leukemia-2 (Bcl-2) were quantified by enzyme immunoassay and Western blot analysis. Oxygen/nitrogen species (ROS/RNS) and total antioxidant capacity (TAC) were analyzed by colorimetric assay. Tissue L-carnitine concentrations were significantly increased in the LCAR group compared to controls. Anti-apoptotic Bcl-2 levels were significantly increased while pro-apoptotic Bax was significantly decreased in LCAR group rats compared to controls. Tissue caspase-3 was significantly alleviated in the LCAR group compared to controls. L-carnitine supplementation increased TAC and decreased ROS/RNS generation in the kidney, liver, stomach and testis tissues compared to controls. Obtained data suggests that L-carnitine supplementation can potentially be used to lessen both oxidative and apoptotic progression in peripheral organs. Highlights: Chronic L-carnitine supplementation regulates protein expression of Bcl-2 and Bax. Chronic L-carnitine supplementation suppresses caspase-3 activity. Chronic L-carnitine supplementation enhances total antioxidant capacity. Chronic L-carnitine supplementation scavenges free radicals.